Improving students' wellbeing at university - Bridgette M. Bewick; Adla Betsaida Martins Teixeira (UFMG, 2021)
This article presents the work done by Leeds University to develop a wellbeing program for students. Dr. Bridgette Bewick, an Associate Professor at School of Medicine, discusses her work on behavioral and psychological understanding of how to improve and support the mental health and wellbeing of university students. She affirms that improvement and support services to students' mental health and wellbeing are necessary but not sufficient to facilitate student success while at university. Dr. Bewick hihglights the urgency to develop practices consistent with pedagogical wellbeing to address student education challenges that have been exacerbated by the Covid-19 pandemic.